Khipu as a bookkeeping record - Małgorzata Czerny (Zeszyty Teoretyczne Rachunkowości)
Purpose: To determine the role of khipu as an accounting record, based on numerical information, in light of current research on khipu (as a system of knotted cords used for record-keeping and communication by the Inca people in the pre-Columbian period).Methodology/approach: This study employs a descriptive analysis and literature review, utilizing methods of interpretation and explanation.Findings: In terms of form, types of records used, and the presentation of information contained therein, khipu is an example of not only arithmetic but also accounting records. The methods by which it was utilized demonstrate the existence of a standardized system of presenting and transmitting accounting information used for data registration and control purposes.Research limitations/implications: The analysis is limited to only a few of the best-preserved archaeological discoveries. In the theoretical part, the considerations are based mainly on ethnographic literature due to the limited number of economic sources.Originality/value: The article presents little-recognized issues in the history of accounting, examining khipu from the perspective of accounting knowledge and management science.